Implementasi Model Concept Learning guna Meningkatkan Prestasi Belajar IPS di SDN 08 Batubara - Fatimah Fatimah; Muhammad Ali Akbar (PT. SORATEKNO PUBSLIHER, 2025)
Students’ academic achievement in Social Studies, particularly on the theme of cultural richness, remains low. This condition is influenced by teaching methods and models that do not sufficiently engage students or support deep conceptual understanding. This study aims to implement concept-based learning to improve students’ academic performance through an effective instructional model. The research is a classroom action research conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection phases. The study involved 25 fifth-grade students of SDN 08 Batubara as research subjects. Data were collected through learning achievement tests, classroom observations, and data analysis.The results show that the application of concept-based learning positively impacted students’ achievement in Social Studies. The initial percentage of students who achieved mastery learning was 48%, which increased to 72% in the first cycle and further improved to 88% in the second cycle. Additionally, student engagement in the learning process also increased, as evidenced by activities such as classifying concepts, participating in discussions, and drawing conclusions independently. Based on these findings, it can be concluded that the Concept Learning model is effective for use in Social Studies instruction, especially in themes that require conceptual mastery, such as cultural diversity. This model also promotes more meaningful and active learning.